Understanding the dental need and care during pregnancy: a review - Ngeow, Wei Cheong; Chai, W.L. (Malaysian Medical Association, 1999)
This paper reviews the oral and dental lesions that are seen during pregnancy. Trimester approach should be adopted in the management of the pregnant patients. A good dental preventive programme is essential. The significance of prescribing fluoride supplements and the use of dental radiography during pregnancy is also briefly reviewed.